EFEKTIVITAS ANGGARAN PENDAPATAN DAERAH KABUPATEN BATU BARA - Elizar Sinambela (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2014)
This study aimed to analyze the effectiveness of local revenues with a case study on Kabupaten Batubara. This study aims to determine the cause of Finance and Asset Management Agency Kabupaten Batubara has not been able to achieve the effectiveness of budget revenues. With the results of this study will be expected to provide input to the regional government in conducting the preparation and analysis of budget revenues based Effectiveness Budget. Data collection techniques in this research is the method of documentation and descriptive approach. The type of data that is used is the type of quantitative data, which is where the data is sourced from secondary data. The results showed that the effectiveness of budget revenues Financial Management Agency Kabupaten Batubara, generally speaking, has not been effective or less effective. Ineffective performance budget revenue that occurred in Kabupaten Batubara due to the lack of effectiveness in the achievement of budget revenue (PAD), especially in the case of not achieving the revenue budget of levies and lack of effectiveness in achieving the revenue that comes from the provincial government transfers funds. To the need for review of the mechanisms of budget preparation and review of the implementation of the system of local revenue realization.